El Aprendizaje de un código de ética universitario: una aproximación experimental en una universidad pública en México - Luis Enrique Segoviano Contreras; Pablo Ignacio Soto Mota (INTER DISCIPLINA, 2026)
This study analyzes, through a randomized experiment with 346 university students, the most effective way to present a university code of ethics to enhance its learning. Four conditions were compared: original language, simplified language, ethical dilemmas, and a control group. The results show that, although there were no significant differences in overall exam performance, the treatments did influence specific levels of learning. The dilemmas treatment improved short-term recall of principles, while the simplified language treatment increased long-term interest in the code within formal settings. Additio- nally, a qualitative analysis suggests that some students perceive the code as insufficient in punitive terms or request greater practical clarity. Overall, the findings highlight the importance of using active pedagogical approaches to strengthen institutional ethics.